2021
DOI: 10.1016/j.agwat.2021.106884
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of soil moisture and canopy cover data improves maize simulation using an under-calibrated crop model

Abstract: Parameter calibration is normally required prior to crop model simulation, which can be a time-consuming and data-intensive task. Meanwhile, the growth stages of different hybrids/cultivars of the same crop often show some similarities, which implies that phenological parameters calibrated for one hybrid/cultivar may be useful for the simulation of another. In this study, a data assimilation framework is proposed to reduce the requirement for parameter calibration for maize simulation using AquaCrop. The pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 85 publications
(99 reference statements)
1
8
0
1
Order By: Relevance
“…Sendo assim, as conclusões são limitadas e dificultam comparações. A despeito disso, estudos sobre valores adequados para os parâmetros de incerteza são necessários, uma vez que a decisão de como atribuir esses valores de incerteza é um problema em aberto e diversos autores a tomam de formas distintas: alguns autores trabalham com erros variáveis [Lu et al 2021], outros usam valores fixos também relacionados aos erros do modelo de conversão [Huang et al 2016], outros estimam com base na variância de observações coletadas em campo [Zhao et al 2013] enquanto outros usam estratégias que independem dessa incerteza [Chen et al 2018;Vazifedoust et al 2009].…”
Section: Assimilação De Dadosunclassified
“…Sendo assim, as conclusões são limitadas e dificultam comparações. A despeito disso, estudos sobre valores adequados para os parâmetros de incerteza são necessários, uma vez que a decisão de como atribuir esses valores de incerteza é um problema em aberto e diversos autores a tomam de formas distintas: alguns autores trabalham com erros variáveis [Lu et al 2021], outros usam valores fixos também relacionados aos erros do modelo de conversão [Huang et al 2016], outros estimam com base na variância de observações coletadas em campo [Zhao et al 2013] enquanto outros usam estratégias que independem dessa incerteza [Chen et al 2018;Vazifedoust et al 2009].…”
Section: Assimilação De Dadosunclassified
“…Numerous past studies have used SDA to constrain crop model estimates, using observations on leaf area index (e.g., Nearing et al, 2012;Ines et al, 2013;Ma et al, 2013;Chen et al, 2018;Lu et al, 2021), soil moisture (Kivi et al, 2022), biomass (e.g., Linker and Ioslovich, 2017) and evapotranspiration (e.g., Huang et al, 2015). For example, a synthetic study by Zhu et al (2017) found that the assimilation of coarse resolution surface soil moisture data into a coupled soil water-groundwater numerical model constrained soil moisture estimates in the first 50 cm of the soil profile despite explicitly unaccounted spatial heterogeneity in soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with , which showed that the EnKF had better yield estimation for maize when calibration was applied prior to LAI data assimilation. In contrast, Lu et al (2021) improved the accuracy of maize yield estimation without prior genotype-specific calibration. In their study, the EnKF method was employed to assimilate canopy cover data for adjusting the phenological parameters of the AquaCrop model for each crop season.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, studies with this methodology in areas where the reduction factors are present, or there would be data flaws in describing the environment, such as soil characterization and climate data, may result in a more pronounced accuracy gain due to the use of DA methods (Gilardelli et al, 2019). Thirdly, other state variables simulated by DS, such as above ground biomass (Lu et al, 2021) plant height , soil moisture , canopy nitrogen accumulation (Li et al, 2015), and canopy cover (Lu et al, 2021) could be also used to enhance the model accuracy. Yet, the used PBM was developed to run without assimilations from start to end, for this study we just adjusted the state variables directly related to the LAI, plant weight, and leaf area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation